2019
DOI: 10.3389/fmicb.2019.02726
|View full text |Cite
|
Sign up to set email alerts
|

Endophytes and Epiphytes From the Grapevine Leaf Microbiome as Potential Biocontrol Agents Against Phytopathogens

Abstract: Plants harbor diverse microbial communities that colonize both below-ground and above-ground organs. Some bacterial members of these rhizosphere and phyllosphere microbial communities have been shown to contribute to plant defenses against pathogens. In this study, we characterize the pathogen-inhibiting potential of 78 bacterial isolates retrieved from endophytic and epiphytic communities living in the leaves of three grapevine cultivars. We selected two economically relevant pathogens, the fungus Botrytis ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 73 publications
(81 reference statements)
2
47
0
1
Order By: Relevance
“…This could further augment the disease protection against BLSB. Bruisson et al [27] reported that "in general, plants are colonized by a variety of microorganisms, some of which (the epiphytes) stay on the surface of plant organs, while others can penetrate further inside the plants and are called endophytes" [27][28][29]. A recent study on the structure and function of the plant microbiome have focused on the host-mediated recruitment and shaping of their rhizosphere microbiome [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could further augment the disease protection against BLSB. Bruisson et al [27] reported that "in general, plants are colonized by a variety of microorganisms, some of which (the epiphytes) stay on the surface of plant organs, while others can penetrate further inside the plants and are called endophytes" [27][28][29]. A recent study on the structure and function of the plant microbiome have focused on the host-mediated recruitment and shaping of their rhizosphere microbiome [42].…”
Section: Discussionmentioning
confidence: 99%
“…Now, the focus has been set on developing microbe-based strategies for the management of devastating pathogens along with resistant cultivars [1,2,[22][23][24][25]. Application of antagonistic endophytic microorganisms is another important aspect of crop protection [26][27][28][29]. The endophyte induces beneficial effects in the plants via a number of complex biochemical signaling processes [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, P. infestans mycelium inhibited by Iturin A (different concentrations) at 20 • C for twelve days was collected with ice-cold sterile water and oscillated to obtain sporangia solution (1 × 10 7 CFU/mL) (Bruisson et al, 2019;Wang et al, 2020). Then, the inhibited sporangia were recovered to release zoospores at 4 • C for 3 h and maintained at 25 • C in the dark for 5 h to complete sporangium direct germination (Hunziker et al, 2015;Bruisson et al, 2019). Also, the sporangia solution (1 × 10 7 CFU/mL) from the mycelium incubated without Iturin A was treated similarly as the control.…”
Section: Antagonism Analysis Of Purified Surfactin and Iturin Amentioning
confidence: 99%
“…Many species belonging to Enterobacter and Pseudomonas ( Meena et al, 2017 ; Zheng et al, 2019 ) are well known plant-beneficial microbes, and Cupriavidus and Phenylobacterium species were reported to participate in the mineralization of soil organic P and degrade organic material ( De La Cruz-Barrón et al, 2017 ). In comparison, P. chinense rhizosphere was enriched with Variovorax , Bosea , and Acinetobacter , and some species of which could inhibit pathogens and supply N for plant growth ( Rilling et al, 2018 ; Bruisson et al, 2019 ), and P. scandens rhizosphere was enriched with Anaeromyxobacter , Frankia , Streptacidiphilus , and Amycolatopsis ( Figure 2 ), with nitrogen-fixing ( Chaia et al, 2010 ) and antimicrobial activity ( Buszewski et al, 2018 ). In summary, although many bacteria are shared among three plant species, each plant still recruits distinctive microbes in rhizosphere, possibly due to their different root exudates.…”
Section: Resultsmentioning
confidence: 99%